Acesso endoscópico transnasal aos tumores selares - Santos, Rodrigo de Paula [UNIFESP] (2007)
Transsphenoidal surgery for sellar region tumors is traditionally done only by neurosurgeons. The use of endoscopes has permitted a direct transnasal approach to the sphenoidal sinus, without dissection of the septal mucosa, reducing postoperative morbidity. AIM: The purpose of this study was to assess the technical difficulties, and per and postoperative complications of the otolaryngological management of the endoscopic transnasal approach to the sellar region. MATERIAL AND METHOD: 159 patients undergoing sellar region surgery between March 2001 and December 2006 were assessed retrospectively. 91 patients who underwent 95 endoscopic transnasal procedures were included in this study. Study design: a clinical retrospective study. RESULTS: The endoscopic transnasal technique was feasible for every patient, independent of age, anatomical variations, tumor characteristics, tumor etiology, and previous surgical history. There was no need to remove the middle turbinate or septal deviations in any of the cases. The most significant peroperative complication was CSF leak during tumor removal (13.68%). Postoperative complications were: nasal bleeding (8.42%), CSF leak (8.42%), and meningitis (2.19). CONCLUSION: The transnasal endoscopic approach was accomplished with minimal invasion, preserving nasal structures in all 95 procedures, independent of age, anatomical variations, tumor characteristics,tumor etiology, and previous surgical history.